2016
DOI: 10.1007/s10567-016-0202-5
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Treatments for Symptoms of Posttraumatic Stress Disorder in Children, Adolescents, and Young Adults: A Meta-Analysis

Abstract: Meta-analyses of the treatment of posttraumatic stress disorder (PTSD) in childhood and adolescence are restricted to specific trauma, selected interventions, and methodologically rigorous studies. This large meta-analysis quantifies the effects of psychological treatments for PTSD symptoms in children and adolescents. An extensive literature search yielded a total of 13,040 articles; 135 studies with 150 treatment conditions (N = 9562 participants) met the inclusion criteria (psychological interventions with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
98
4
10

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 159 publications
(126 citation statements)
references
References 31 publications
14
98
4
10
Order By: Relevance
“…The analysis of pre-post effects confirmed the positive effects for CBT, but there were some other treatments with positive pre-post effects that might be promising candidates for future investigation: EMDR, meditation-relaxation, an educational programme in schools as developed by the UNESCO, a stepped systemic treatment designed to the needs of young refugee youth, and writing for recovery. The positive CBT and EMDR effects are in line with the recent literature on youth from the general population (Gillies, Taylor, Gray, O’Brien, & D’Abrew, 2013; Gutermann et al, 2016). The mean pre-post effect size in our study cannot be meaningfully interpreted due to the high heterogeneity, which has also been reported in a number of other meta-analyses (e.g.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The analysis of pre-post effects confirmed the positive effects for CBT, but there were some other treatments with positive pre-post effects that might be promising candidates for future investigation: EMDR, meditation-relaxation, an educational programme in schools as developed by the UNESCO, a stepped systemic treatment designed to the needs of young refugee youth, and writing for recovery. The positive CBT and EMDR effects are in line with the recent literature on youth from the general population (Gillies, Taylor, Gray, O’Brien, & D’Abrew, 2013; Gutermann et al, 2016). The mean pre-post effect size in our study cannot be meaningfully interpreted due to the high heterogeneity, which has also been reported in a number of other meta-analyses (e.g.…”
Section: Discussionsupporting
confidence: 85%
“…Recent meta-analyses on PTSD treatment in children and adolescents after various kinds of trauma show converging evidence with overall effect sizes of g = 0.83 and 0.89 when compared to waitlist and of g = 0.41 and 0.45 when compared to active controls (Gutermann et al, 2016; Morina, Koerssen, & Pollet, 2016; respectively). Effect sizes for depression were 0.60 and for anxiety 0.67 when compared to waitlist, and 0.37 and 0.42 in comparison to active controls (Gutermann et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the aftermath of major natural disasters, acute stress reactions are expected, and overall resilience is the rule rather than the exception. Many studies have shown that 1–6 months post-trauma, PTSD is reduced by approximately 50%; nevertheless, there are doubts as to whether there is further reduction of PTSD after 6 months post-trauma.A large recent meta-analysis showed that psychotherapy for PTSD symptoms has a small or large effect size depending on the control group; cognitive behavioural therapy has the highest effect sizes, especially in individual therapy with parental involvement (Gutermann et al, 2016). Key components of effective treatment are psychoeducation about trauma reactions, exposure to trauma-related cues and memories until they become habituated, coping skills training for children to help them to manage their anxiety, and parental training to help them to facilitate their children’s recovery.…”
mentioning
confidence: 99%
“…A large recent meta-analysis showed that psychotherapy for PTSD symptoms has a small or large effect size depending on the control group; cognitive behavioural therapy has the highest effect sizes, especially in individual therapy with parental involvement (Gutermann et al, 2016). Key components of effective treatment are psychoeducation about trauma reactions, exposure to trauma-related cues and memories until they become habituated, coping skills training for children to help them to manage their anxiety, and parental training to help them to facilitate their children’s recovery.…”
mentioning
confidence: 99%